konseling sufistik dalam perspektif syaikh abdul shamad Al-Palimbani - Permata Puncak; Saepuddin; Jhonsi hunandar (Program Studi Tasawuf dan Psikoterapi, 2026)
This study discusses the concept of Sufistic counseling from the perspective of Syaikh Abdul Shamad al-Palimbani, one of the prominent 18th-century Nusantara scholars who significantly contributed to the development of Sufi teachings. Through a literature review of his works, particularly Hidayatus Salikin and Siyarus Salikin, this research reveals al-Palimbani’s views on the processes of soul purification, spiritual strengthening, and inner healing as the foundations of Sufistic counseling. The findings show that Sufistic counseling according to al-Palimbani emphasizes three main aspects: (1) tazkiyatun nafs through mujahadah and riyadhah as forms of self-purification; (2) the deepening of ma'rifat to build divine consciousness as the core of psychological strength; and (3) the formation of noble character as a manifestation of spiritual perfection that contributes to mental well-being. These concepts are relevant to be integrated into modern counseling practices, especially within Muslim communities that require a tradition-based spiritual approach. This study asserts that al-Palimbani’s ideas can serve as a holistic model of Sufistic counseling, harmoniously combining psychological and spiritual dimensions. Keywords: konseling, sufistik, syaikh abdul shamad